(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article highlights the factors that awaken fear and panic attacks. The theoretical foundations of the emotional and physiological manifestation of fear, panic attacks, and factors that predispose to them are analyzed. Natural and acquired aspects of phobias and fears are considered. The article is intended for students of psychological and medical faculties, as well as for those interested in the problem of emotional states of the individual.